Health Care Transition of Adolescents and Young Adults with Haemophilia: the Situation in Germany and the Munich experience - Bidlingmaier, Christoph; Olivieri, Martin; Schilling, Freimut H.; Kurnik, Karin; Pekrul, Isabell (Hämostaseologie, 2020)
Patients suffering from haemophilia encounter various phases in life, in which individual needs, life situations, and self- and disease perception change rapidly. One of these phases spans from the beginning of puberty until early adulthood, in which individuals gain self-responsibility and reach independence and autonomy. In this challenging time that determines future health, adolescents and young adults need sustainable familiar and professional support. A change in health care team and treatment centre may expose adolescent patients to threats but also provides the possible opportunity to be well prepared. While there is emerging evidence that the so-called health care transition programmes are effective in maintaining quality of care in other disease areas, transition programmes for patients with haemophilia are still rare in Germany, and the evidence is limited. We describe the situation in Germany, discuss our experience in Munich and review some of the available guidance; we conclude that transition programmes should become a standard of care in haemophilia.
Keywords: haemophilia; transition; medical; psychosocial